REVIEW ON ANTIVIRAL AND IMMUNO-STIMULATORY POTENTIAL OF MEDICINAL PLANTS - Kumar, *Manoj; Dr, Anjay (International Journal of Ayurveda and Pharma Research, 2016)
Research on medicinal plants has attracted a lot of attention globally in past few years. A wide variety of active phytochemicals, including the flavonoids, terpenoids, lignans, sulphides, polyphenolics, coumarins, saponins, furyl compounds, alkaloids, polyines, thiophenes, proteins and peptides of plants and herbs have been identified for its medicinal and antiviral properties. Some volatile essential oils of commonly used culinary herbs, spices and herbal teas have also exhibited a high level of antiviral activity. However, given the few classes of compounds investigated, most of the pharmacopoeia of compounds in medicinal plants with antiviral activity is still not known. Several of these phytochemicals have complementary and overlapping mechanisms of action, including antiviral effects by either inhibiting the formation of viral DNA or RNA or inhibiting the activity of viral reproduction. Assay methods to determine antiviral activity include multiple-arm trials, randomized crossover studies, and more compromised designs such as non randomized crossovers and pre and post-treatment analysis. Methods are needed to link antiviral efficacy or potency and laboratory based research. However, relative success achieved recently using medicinal plant/herb extracts of various species that are capable of acting therapeutically in various viral infections has raised optimism about the future of phyto-antiviral agents. In this review we illustrates, innumerable potentially useful medicinal plants and herbs waiting to be evaluated and exploited for therapeutic applications against genetically and functionally diverse viruses families such as Retroviridae, Hepadnaviridae, Poxviridae, Reoviridae and Herpesviridae.